Analisis Pengaruh Karakteristik Budaya Organisasi terhadap Kepuasan Kerja Karyawan - Rozikin, Zainur (Universitas Brawijaya, Indonesia, 2008)
This research discusses about the influence of organizational culture characteristic toward working satisfaction of the employee. Objectives of this research are to analyze influence of organizational culture characteristic variable that comprises of individual initiative, tolerance to risk, briefing, integration, managerial support, monitoring, identity, reward system, tolerance to conflict, as well as communication pattern toward working satisfaction of the employee. Second, it is also to analyze variable of the organizational culture characteristics which has the most dominant influence toward working satisfaction of the employee. Results of the research show that in accordance to the model testing, the organizational culture characteristics that include individual initiative, tolerance to risk, briefing, integration, managerial support, monitoring, identity, reward system, tolerance to conflict, and communication pattern have significant influence toward working satisfaction of the employee. The second hypothesis testing on the managerial support that has dominant influence toward working satisfaction of the employee is accepted orÂ proven.